Workforce agility: a systematic literature review and research agenda - Alviani, Devi; Hilmiana,; Widianto, Sunu; Muizu, Wa Ode Zusnita (Frontiers in Psychology, 2024)
Introduction The definition and operationalization of workforce agility, initially associated with multitasking abilities, have evolved to encompass aspects of adaptability, proactivity, and resilience, which are now widely accepted. However, some authors have expanded this concept by adding elements such as intelligence, collaboration, and social support, leading to confusion and disagreement on how to consistently measure workforce agility. Furthermore, the literature emphasizes the importance of workforce agility in achieving business goals and adopting innovative management models, yet it provides limited structured guidance for future research. Methods This study uses Scopus and Web of Science as the primary databases. The search was not limited to a specific period but included articles up to 2024, with an initial sample of 176 articles. After a screening process based on inclusion and exclusion criteria, 74 articles were included in the thematic analysis and data synthesis. Results Workforce agility has been positioned as an independent, mediating, moderating, and dependent variable in various studies. Most studies examine workforce agility at the individual level, with only about 10 studies exploring this aspect at the organizational level. However, no research has specifically explored workforce agility at the team level to date. The primary objective of workforce agility research is to expand and connect theories with diverse methodological approaches, including quantitative, qualitative, and mixed methods. As a result, theoretical foundations and inter-variable relationships are established to identify recommendations for future research. Discussion More than 25 fundamental theories have been identified and categorized into nine groups. These nine groups were then reformulated into four general theories: Organizational and Management Theory, Communication and Social Interaction Theory, Behavioral and Learning Theory, and Economic Theory. Based on previous research, several recommendations for future research have been outlined, including conducting longitudinal studies, integrating mixed methods, considering the global cultural context, expanding research samples, developing conceptual models, exploring mediating and moderating variables, developing workforce agility theories, creating efficient evaluation methods, and implementing multilevel models.